2017
DOI: 10.1021/acsphotonics.7b00852
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient and Stable Narrow-Band Red Phosphor Cs2SiF6:Mn4+ for High-Power Warm White LED Applications

Abstract: Due to the unique narrow-band red emission and broadband blue light excitation, as well as milder synthesis conditions, Mn 4+ ion activated fluoride red phosphors show great promise for white light emitting diode (W-LED) applications. However, as the Mn 4+ emission belongs to a spin-forbidden transition ( 2 E g → 4 A 2 ), it is a fundamental challenge to synthesize these phosphors with a high external quantum efficiency (EQE) above 60%. Herein, a highly efficient and thermally stable red fluoride phosphor, Cs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
91
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(93 citation statements)
references
References 55 publications
1
91
0
Order By: Relevance
“…[22][23][24][25][26][27][28][29][30][31][32] Recently, it was reported that Mn 4+ ions with a far-red emission of around 710 nm can also be used for plant cultivation LEDs because the emission range due to the 2 E g / 4 A 2g transition was in accordance with the absorption band of phytochrome P FR (centers at 730 nm). 33 Moreover, the Mn 4+ ion can be excited by both blue and near-ultraviolet (NUV) LED chips and exhibits wide absorption bands, which broaden the application eld.…”
Section: -15mentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29][30][31][32] Recently, it was reported that Mn 4+ ions with a far-red emission of around 710 nm can also be used for plant cultivation LEDs because the emission range due to the 2 E g / 4 A 2g transition was in accordance with the absorption band of phytochrome P FR (centers at 730 nm). 33 Moreover, the Mn 4+ ion can be excited by both blue and near-ultraviolet (NUV) LED chips and exhibits wide absorption bands, which broaden the application eld.…”
Section: -15mentioning
confidence: 99%
“…11,14 Owing to the advantages in this field, Mn 4+ -doped red phosphors have drawn much attention. 20 Nevertheless, fluoride phosphors not only suffer from instability under moisture environment but also endanger the environment usually due to the employed toxic HF solution in the synthesis process. [15][16][17] Among Mn 4+ -doped red phosphors, fluoride compounds usually exhibit efficient sharp emission peaking at ~630 nm.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Among Mn 4+ -doped red phosphors, fluoride compounds usually exhibit efficient sharp emission peaking at ~630 nm. Thus, warm WLED can be reached by employing Mn 4+ -activated fluoride phosphors plus YAG:Ce 3+ , which has been demonstrated in many cases, including K 2 SiF 6 :Mn 4+ , 16 20 Nevertheless, fluoride phosphors not only suffer from instability under moisture environment but also endanger the environment usually due to the employed toxic HF solution in the synthesis process. These problems should be further concerned.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the commercial fabrications of w‐LEDs usually employ the strategy that combines InGaN blue chips and the Y 3 Al 5 O 12 :Ce 3+ (YAG:Ce 3+ ) yellow phosphor . However, the well‐known shortcomings are the high color temperature (CCT, > 6000 K) and low color rendering index (CRI, R a < 80), caused by the emission deficiency in the red region . These shortcomings hinder the residential application of the w‐LEDs in daily life.…”
Section: Introductionmentioning
confidence: 99%